Faktor-Faktor Penentu Kualitas Audit: Tinjauan Sistematis atas Peran Kompetensi Auditor, Profesionalisme, Teknologi Kecerdasan Buatan, dan Dinamika Hubungan Klien: Literature Review - Suherman, Lukas Pamungkas; Nugrahanti, Trinandari Prasetya (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The objective of this study is to examine the determinants of audit quality. The research method employs a Systematic Literature Review (SLR) approach, using a literature search strategy based on keywords in Scopus and Google Scholar, along with the establishment of inclusion and exclusion criteria to filter relevant literature. The findings indicate that the quality of audit is influenced by both internal and external factors. Internal factors include auditor competence and professionalism, while external factors involve the use of artificial intelligence and maintaining a balanced professional relationship between the auditor and the client. This study recommends strengthening competence, ethics, and the use of technology in audit practices.